Pastoralism and Conflict Transformation in Nyangatom, Hammer, and Dassanech Community of Ethiopia - Alemneh, Asmare Shetahun; Alemu, Astatike (Journal of Social Transformation and Regional Development, 2023)
This study examined the practices of conflict transformation in Nyangatom, hammer, and Dassanech community of South Omo Zone Ethiopia using Qualitative research methodology, case study research design and employed FGD, semi structured interview, non-participant observation and document analysis. The issue of conflict transformation traced back to the works of Lederach in the 1980s and Galtung in the late 1970s. The concept, however, gained recognition because of the coming of the issue of human security by the international community and scholars. The nature of pastoralist and agro pastoralist conflicts arising in the study area led to examine the practices of the conflict transformation by various actors. This study indicated that the various actors working on conflict and peace do a very little activity to transform conflicts. They focus on conflict management, prevention, and resolution activities. This has been as a result of lack of attention to plan the issue of conflict transformation by the government. This study, therefore, sought to find out the role of the various actors in conflict transformation. The findings show those grievances, animal raiding, land claims, fishing rights, competition on water and pasture resources use are the sources of conflict. The study also examines the practices of conflict transformation activities in the study area. Resilience, rangeland management, NGOs intervention in peace dialogue, integration of pastoralism and agro pastoralism with commercial agricultures, drought and conflict early warning system, water resource management and development, development, rehabilitations of range land, and providing education to the conflict affected community are the activities done for conflict transformation. These activities had been instrumental in addressing conflicts and transforming relationships. The pastoralist conflict transformation and peace are not given emphasis by the government. The activities are not enough to transform conflicts but they are served as the driver of peace. The researcher recommends that the current conflict transformation mechanism tried in the area is did not change the conflict situation but the beginnings are goodly appreciated.